51.5 W monolithic single frequency 1.97 mbmu m Tm-doped fiber amplifier. (14th February 2014) - Wang, Xiong; Zhou, Pu; Wang, Xiaolin; Xiao, Hu; Si, Lei
Abstract: We demonstrate a monolithic single frequency Tm-doped fiber amplifier with output power of 51.5 W. A single frequency fiber laser at 1.97 mmu m is amplified by a cascaded master oscillator power amplifier (MOPA) system with all-fiber configuration. The optical-to-optical conversion efficiency of the main fiber amplifier is 45%. No amplified spontaneous emission (ASE) or stimulated Brillouin scattering (SBS) effect is observed in the fiber amplifier. The output power could be further scaled by launching more pump power.